PENGARUH SIZE, FREE CASH FLOW, DISCRETIONARY EXPENSE RATIO, ROA, TOBINS Q, LEVERAGE RATIO, TERHADAP STICKY COST BEHAVIOR PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015 - dumaris sidabutar; khairunnisa harahap; akmal huda nasution (Universitas Negeri Medan (UNIMED), 2018)
The problem in this research is that sticky cost behavior can bring adverse effects for companies where the higher level of sticky cost behavior in the company then the company will more difficult to achieve profit. This study aims to determine the indication of Sticky cost behavior in manufacturing companies listed on the IDX period 2013-2015 and to see whether the behavior of sticky cost is influenced by Size, Free Cash Flow, Discretionary Expense Ratio, Return on Assets, Tobins'Q, and Leverage.The population used in this study are all manufacturing companies listed on the BEI in 2013-2015. Of the 143 listed companies, 89 sample companies were selected using purposive sampling method. The data used in this study is secondary data, by downloading financial statements (Financial Report) from the website www.idx.co.id. Hypothesis test in this study using ABJ model which is a modification of multiple linear regression model introduced by Anderson, Balakhrisman, Janakiraman (2003).The result of hypothesis testing shows that there is indication of sticky cost behavior at manufacturing company in BEI. simultaneously show that. Size, Free Cash Flow, Discretionary Expense Ratio, Return on Assets, Tobins'Q, and Leverage influence sticky cost behavior. only partially Tobins'Q has effect Gradually Sticky cost behavior. This means that the higher tobins'Q indicates the company is less able to manage the cost properly so that the cost of Sticky increased. while Size, Free Cash Flow, Discretionary Expense Ratio, Return onAsset, and Leverage have no effect on Sticky cost behavior. This means that if Size, Free Cash Flow, Discretionary Expense Ratio, Return on Asset, and Leverage increase then the company is able to adjust the cost well in accordance with the movement of sales resulting in sticky costs can be overcome in other words sticky cost will be lower.The conclusion of this research is that there are indications of sticky cost behavior on manufacturing companies in BEI and Size, Free Cash Flow, Discretionary Expense Ratio, Return on Assets, Tobins'Q, and Leverage simultaneously affect the behavior of sticky cost.